THE EFFECT OF USING AUDIO VISUAL MEDIA ON FLOOD DISASTER PREPAREDNESS KNOWLEDGE AT ST ANTONIUS MATARAM SMP - Astuti, Febriati; Wijaya, Alwan; Partiwi, Kadek Dwi; Ilmi, Nurul; Putra, Ageng Abdi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Flood disaster is one type of natural disaster that very often occurs in Indonesia, Indonesia experienced flood events according to the Indonesian Disaster Information Data (DIBI) for the last 5 years as many as 4031 times and in the province of West Nusa Tenggara (NTB) it showed a number of 111 flood events with One of them was Mataram city which experienced 11 incidents and West Lombok flooded 26 times. Disaster prevention is one of the focuses in schools by empowering teenagers to understand knowledge about disaster preparedness in students as one solution that needs to be done because children are one of the vulnerable groups who are at risk of being affected by disasters. The purpose of this study was to determine the effect of using Audio Visual media on knowledge of flood disaster preparedness at SMPK ST Antonius Mataram.The population in this study were students in grades VII and VIII, totaling 62 people. The sample in this study as many as 58 people with a sampling technique that is purposive sampling with inclusion and exclusion criteria. The research design used in this study was pre-experimental through a one group pre-test-post-test design approach. Data collection techniques using questionnaires. Analysis of this data using statistical test data analysis Wilcoxon signed rankings test.Based on the results of the study, there was an effect of using Audio Visual media on knowledge of flood disaster preparedness at SMPK ST Antonius Mataram.